2019
DOI: 10.1088/2058-6272/aaeba6
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening decomposition of oxytetracycline in DBD plasma coupling with Fe-Mn oxide-loaded granular activated carbon

Abstract: A catalytic approach using a synthesized iron and manganese oxide-supported granular activated carbon (Fe-Mn GAC) under a dielectric barrier discharge (DBD) plasma was investigated to enhance the degradation of oxytetracycline (OTC) in water. The prepared Fe-Mn GAC was characterized by x-ray diffraction and scanning electron microscopy, and the results showed that the bimetallic oxides had been successfully spread on the GAC surface. The experimental results showed that the DBD+Fe-Mn GAC exhibited better OTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Mn(III)/Mn(II) played an important role in the MB degradation process and contributed to ideal MB degradation in C, N-doped MnO. Present obtained MnO nanomixtures demonstrated potential applications in self-assembled materials design and composites for wide applications [54,55,56,57,58,59,60,61,62,63,64,65].…”
Section: Resultsmentioning
confidence: 89%
“…Mn(III)/Mn(II) played an important role in the MB degradation process and contributed to ideal MB degradation in C, N-doped MnO. Present obtained MnO nanomixtures demonstrated potential applications in self-assembled materials design and composites for wide applications [54,55,56,57,58,59,60,61,62,63,64,65].…”
Section: Resultsmentioning
confidence: 89%
“…supported iron and manganese oxides on granular activated carbon, showed similar performance under DBD plasma for the degradation of oxytetracycline in water. 280 Compared to individual oxides it has been concluded that the supported oxides could better catalyze the O3 decomposition into active HO•, HO2• and O 2radicals responsible for the enhanced degradation of oxytetracycline, even though the oxidation is leading to a mixture of degradation compounds in the final treated water.…”
Section: Decontamination Of Waters Polluted With Pharmaceuticals By P...mentioning
confidence: 99%
“…However, their efficiency declines when the solution to be treated contains a high concentration of organic matter and mineral salts, which can originate an inhibition or competition effect for the plasma-generated oxidant species. 279 Therefore, coupling plasma with a catalyst is expected to produce a more efficient pollutant degradation 280 with the condition that the catalyst is not affected/damaged by plasma-generated reactive species. Therefore, the dosage of the key species, such as the O atom, and quite oxidizing species such as HO − , O 2 − , or HO 2 − generated by direct discharges in water (Figure 31) affording an advanced liquid oxidation rather than less aggressive O 2 , O 3 , or NO, obviously also part of the plasma activated oxygen, might be optimized by the presence of catalysts.…”
Section: Plasma-catalytic Processes Utilized In the Decontamination O...mentioning
confidence: 99%
“…Some bands at 576, 617, 887, and 1290 cm −1 were formed after the sequential experiments, which explained the participation of oxidants and the generation of derived Fe and Mn species. 65,75,76 Fewer peaks were found in the spectrum of specimens acquired from the coupling experiments. The MW combined with oxidant participation was more conducive to strengthening the effect of acid leaching on the U extraction from the U tailing specimens.…”
Section: Changes In Mineralmentioning
confidence: 99%